Autumn Solid Waste Characterization in the Seyitler Campus of Artvin Çoruh University - Kazım Onur Demirarslan; Emre Aydın; Mehmet Ali Aydın (Doğal Afetler ve Çevre Dergisi)
In parallel with the recent developments in population growth, urbanization, industrialization, a rising in environmental problems has also been observed. Among these environmental problems mentioned, air, water and soil pollution caused by solid wastes attract attention in particular. Unless the waste management system is appropriately guided, managements will be faced with exponentially increasing waste load every year. The waste produced should be collected and appropriately disposed by the local governments at the source. In addition to solid waste generated domestically, the solid waste produced in public buildings of our country also constitute an important place. Especially in educational places such as schools and universities, it is highly probable that high economic value wastes are formed. In this study, the qualities of the solid wastes generated in the Seyitler Campus of Artvin Çoruh University were examined. The study was conducted in four locations between 19.10.2016 and 14.12.2016, during the continuation of education to represent the fall semester. In the sortation process of the waste composition, it was determined that the wastes collected from the campus consisted of 42,77 % organic, 7,23 % paper, 6,19% plastic, 4,37% glass and 0,39% metal, 1,09% textile, 37,79% septic personal use. The aim of the study is to provide a general benefit on how the characteristics of time, quantity and waste can be evaluated in carrying out waste management plans in the future by focusing on recycling.